Prevalence of Hypokalemia in Diabetic Ketoacidosis Patients Presenting to the Emergency Department: Hypokalemia in Diabetic Ketoacidosis Patients - Siddiqui, Noor us Sahar; Ahmed, Meer; Sikhandar, Sanober; Memon, Shahdil Zulfikar; Fatima, Farina; Aakash, Aakash (Pakistan Journal of Health Sciences, 2024)
Diabetic Ketoacidosis (DKA) is a potentially life-threatening hyperglycemic emergency that leads to severe metabolic derangements which may cause low potassium concentrations, resulting from insulin and hence a poorer outcome among patients admitted in emergency departments. Objective: To determine the prevalence and severity of hypokalemia in patients with Diabetic Ketoacidosis (DKA) presenting to the emergency department. Methods: A cross-sectional study was conducted at the Department of Emergency Medicine of Jinnah Postgraduate Medical Centre, Karachi from November 2022 to April 2023. 97 patients with a blood glucose level of 250 mg/dL or higher at the time of arrival and aged between 18 and 65 years were included in the study, using consecutive sampling, meeting the diagnostic criteria for DKA. Results: The prevalence of hypokalemia was 53.61% (n=52). Within this group, 39.18% had mild hypokalemia, 11.34% had moderate hypokalemia, and 3.09% had severe hypokalemia. Conversely, 45.36% of patients maintained normal potassium levels, while only 1.03% presented with hyperkalemia. Furthermore, among those with hypokalemia, 53.16% were using insulin, with a p-value of 0.082 indicating no significant association with insulin use. In terms of gender, 30 males (53.57%) and 22 females (42.31%) experienced hypokalemia, but this was also found to be statistically insignificant (p=0.42). Conclusions: This research revealed that significant prevalence of hypokalemia in diabetic ketoacidosis (DKA), with 53.61% of participants affected (3.1% of cases exhibited severe hypokalemia), highlighting the importance of adhering to the American Diabetes Association’s recommendation to assess serum potassium levels before initiating DKA treatment.